Oxidant status, iron homeostasis, and carotenoid levels of COPD patients with advanced disease and LTOT. Issue 1 (1st January 2018) - Kentson, M.; Leanderson, P.; Jacobson, P.; Persson, H. L.
ABSTRACT: Background : The pathogenesis of chronic obstructive pulmonary disease (COPD) is associated with oxidative stress. Both iron (Fe) and oxygen are involved in the chemical reactions that lead to increased formation of reactive oxygen species. Oxidative reactions are prevented by antioxidants such as carotenoids. Objective : To study the differences in Fe status, carotenoid levels, healthy eating habits, and markers of inflammation and oxidative damage on proteins in subjects with severe COPD ± long-term oxygen therapy (LTOT) and lung-healthy control subjects. Methods : Sixty-six Caucasians with advanced COPD (28 with LTOT) and 47 control subjects were included. Questionnaires about general health, lifestyle, and dietary habits were answered. Lung function tests and blood sampling were performed. Results : COPD subjects (±LTOT) did not demonstrate increased oxidative damage, assessed by protein carbonylation (PC), while levels of soluble transferrin receptors (sTfRs) were slightly elevated. Soluble TfRs, which is inversely related to Fe status, was negatively associated with PC. Levels of carotenoids, total and β-cryptoxanthin, α- and β-carotenes, were significantly lower in COPD subjects, and their diet contained significantly less fruits and vegetables. Lutein correlated inversely with IL-6, lycopene correlated inversely with SAT, while β-carotene was positively associated with a Mediterranean-like diet. Conclusions : Fe could favor oxidative stress in COPD patients, suggesting a cautious use of Fe prescription to these patients. COPD subjects ate a less healthy diet than control subjects did and would, therefore, benefit by dietary counseling. COPD patients with hypoxemia are probably in particular need of a lycopene-enriched diet.